Distribution and extent of electronic medical record utilisation in eye units across the United Kingdom: a cross-sectional study of the current landscape. Issue 5 (17th May 2017) - Lim, Shin Bin; Shahid, Humma
Abstract : Objectives: Ophthalmology units across the UK vary widely in their adoption of electronic medical records (EMR). There is a lack of evidence to show the extent and progress of EMR adoption. The aim of this study was to capture a snapshot of the current landscape of EMR use, as a baseline for comparison in future studies. Setting: An electronic survey questionnaire was sent to all NHS ophthalmology Units in the UK. Participants: A total of 104 National Health Service (NHS) ophthalmology units participated in the survey, which was carried out over 6 months from December 2013 to June 2014. Primary and secondary outcome measures: Respondents were asked about technology usage pertaining to specific processes in the clinic workflow. This allowed us to determine the extent of EMR usage and details about current use or planned implementation by each unit. Results: 77.6% (n=104) of NHS ophthalmology units responded. 45.3% (n=48) of units were currently using an EMR and a further 26.4% (n=28) of units plan to implement EMR within 2 years. 70.8% of units with a current EMR system use Medisoft. EMR is used by all clinicians in 37.5% and by all subspecialties offered at the unit in 27.0%. In 56.3%, new clinical notes are entered into EMR only by clinicians. All imaging devices are networked to EMR in 28.3%. In 46.7%, EMR is accessible by other specialties within the same hospital. 71.1% would recommend EMR to a colleague. Conclusions: EMR has the potential to address current limitations of patient information transfer and sharing in ophthalmology. It is pleasing to see a significant proportion of units already engaging with EMR or having plans to do so in the near future. However, differing EMR systems and lack of remote access mean further optimisation of these record systems are needed to allow data transfer between units.